Variation in duplex peak systolic velocity measurement in a multi-site vascular service. (November 2015) - Normahani, P; Aslam, M; Martin, G; Standfield, NJ; Jaffer, U
Objective: Duplex US (DUS) is increasingly utilised as a first-line investigation for the assessment of carotid disease. For clinical decision-making, DUS assessment must be accurate and reproducible to ensure reliability. We aimed to investigate the variability in peak systolic velocity (PSV) measurement in a multi-site vascular network. Methods: DUS measurements of PSV were taken from continuous and pulsatile flow, generated by a high fidelity phantom, by 12 experienced vascular scientists across four hospitals. Participants were blinded to the actual PSV value (50 cm/s). Results: We observed an average error of 13.2% (± 8.3) and 11.6% (± 7.5) in PSV measurements taken from pulsatile and continuous waveforms, respectively. Measurements of PSV using the pulsatile waveform demonstrated statistically significant variation across all hospitals; ((hospital/mean) A 43.9 cm/s, B 61.7 cm/s, C 57.4 cm/s, D 47.7 cm/s, p=0.001). Further analysis demonstrated statistically significant variation in 4 instrumentation-related factors when measuring from a pulsatile waveform (Doppler angle, angle of insonation, velocity range, scale range). Conclusion: We observed a significant level of error and variation in PSV measurements across four sites within our vascular network. Variation in instrumentation-related factors may be accountable for this. In light of the centralisation of vascular services, it is increasingly important to unify and implement scanning protocols in order to reduce error and inter-site variability.